DENTAL IMPLANT TREATMENT IN THE POSTERIOR MAXILLA - J Bublík; P Michl (Czech Dental Chamber, 2022)
Introduction and aim: Dental implant treatment in the posterior maxilla is often complicated by the poor healing of the alveolar process and by the pneumatization of the maxillary sinus. The authors are explaining the Cologne Classification of the Alveolar Ridge Defects (CCARD) with special emphasis on the maxillary sinus area and listing the main fators influencing process of selection of dental implant treatment. The aim of this article is to demonstrate, using case reports, four types of treatment. Results and conclusions: There are four types of treatment implant surgeon must choose from while considering treatment in posterior maxilla. Current literature does not give a guidance as to which treatment method to use. Transalveolar sinus lift has a good clinical outcome regardless of presence or absence of grafting material. Short implants with a long clinical crown are good alternative to treatment at times where Schneiderian membrane manipulation is not advised.